1999
DOI: 10.1088/0026-1394/36/6/2
|View full text |Cite
|
Sign up to set email alerts
|

New, fully automated, primary standard for generating vacuum pressures between 10 10Pa and 3   10 2Pa with respect to residual pressure

Abstract: A new primary standard for the realization of vacuum pressures between 10 -10 Pa and 3 ϫ 10 -2 Pa has been completed at the Physikalisch-Technische Bundesanstalt (PTB). It is based on the continuous expansion method, whereby the range is extended to lower pressures by the use of a flow divider. In this flow divider, the gas flow from the fully automated flowmeter with throughputs ranging from 10 -6 Pa l/s up to 3 Pa l/s (at 23 C) is directed via two differently sized orifices into two chambers: the XHV calibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 9 publications
0
37
0
1
Order By: Relevance
“…The primary standard at PTB is a continuous expansion system, called CE3 [3], with its flowmeter FM3 [4]. Known gas flow is injected into a flow divider chamber, which then flows into either a UHV chamber through a larger conductance orifice or into a XHV (extreme high vacuum) chamber through a smaller conductance orifice with about 1/100 of the conductance to the UHV chamber.…”
Section: Dynamic Expansion Standard At Ptbmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary standard at PTB is a continuous expansion system, called CE3 [3], with its flowmeter FM3 [4]. Known gas flow is injected into a flow divider chamber, which then flows into either a UHV chamber through a larger conductance orifice or into a XHV (extreme high vacuum) chamber through a smaller conductance orifice with about 1/100 of the conductance to the UHV chamber.…”
Section: Dynamic Expansion Standard At Ptbmentioning
confidence: 99%
“…The leak was immediately redressed. Also it was found that the small orifice C 02 [3] (nominal diameter 700 µm) from the flow divider into the XHV chamber was dented and had changed its dimension, probably due to a high differential pressure during a pump down process after venting. The conductance was re-measured.…”
Section: Dynamic Expansion Standard At Ptbmentioning
confidence: 99%
“…Jousten [12] s Calibrated bellows 12 5 Â 10 À 6 0.05 0.15 Jitschin [13] s Pistonþ lubricated o-rings 25 5 Â 10 À 4 50 0.1 Li [14] s/r Pistonþ bellows þ oil-filled cylinder 10, 25 5 Â 10 À 6 13 2. Jousten [15] s Calibrated bellows 12 5 Â 10 À 7 13 0.2 Jousten [16] s Calibrated bellows 12 5 Â 10 À 7 13 0.14 Calcatelli [17] s Pistonþ cylinderþ custom PTFE seal 5, 20 1 Â 10 À 5 0.7 0.2 Berg [18] s/r Pistonþ bellows þ oil-filled cylinder 102 1 Â 10 À 1 270 0.02 Cignolo [19] s/r Pistonþ lubricated o-ring 120 9 Â 10 À 2 1900 0.01 Kramer [20] s/r Double piston 16 1 Â 10 À 3 1.3 0.03 Cheng [21] s Pistonþ bellows þ oil-filled cylinder ? 5 Â 10 À 6 0.05 0.57 Gronych [22] s Calibrated bellows 9,30 3 Â 10 À 4 55 1.…”
Section: Reference S/r Typementioning
confidence: 99%
“…The third type of flow standard, calibrated bellows [12,15,16,22], also has no sliding seal, and it eliminates the complications due to the oil by driving the bellows directly. Its chief disadvantage is that the bellows volume V(x) must be calibrated as a function of its linear displacement x. Jousten et al [12] found that V(x) was more linear for a formed bellows than for a welded diaphragm bellows, although Gronych et al [22] later were able to use a welded diaphragm bellows despite its nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…Such devices are, generally, made of a calibration chamber connected to the pumping chamber through a conductance. The pumping system is, frequently, a combination of mechanical and turbo molecular pumps and the conductance is as near as possible to a hole in a thin wall to be able to calculate its value by analytical [98,99] or by Monte Carlo methods [100,101].Those systems need to be equipped with a gas flow generating and measuring unit that is frequently based on the variable-volume and constant-pressure method [102,103]. In the simple realization the lower limit may be between 10-6 and 10-7 Pa. For lower pressure, on the historical point of view it should be mentioned the PTB molecular beam system realized several years ago by G. Messer and G. Grosse [104,95].…”
Section: Needs Of Calibrationsmentioning
confidence: 99%